On the three explosion limits of an H2–O2 system and their relationships to ignition delay. (20th April 2017) - Lidor, A.; Weihs, D.; Sher, I.; Sher, E.
Abstract: We propose a unified model for the three branches of the explosion limits of an H2 –O2 mixture. By using different expressions for the ignition delay time at each limit, and by utilizing the Le-Chatelier rule, we obtain an analytical expression for the ignition delay time of the mixture. We show that by solving the time delay equation for a selected typical ignition delay time we obtain a single expression for the Z-shape explosion limits. Highlights: We study the three-zones explosion limits of an H2 –O2 System. We assume the limits are dominated by chain-carriers production/removal mechanism. We propose a relationship between the time delay and the explosion limits of an H2 –O2 system. We use the Le-Chatelier rule to obtain a single expression for the Z-shape explosion limits.